RETRACTED ARTICLE: Pre-activation of mesenchymal stem cells with TNF-α, IL-1β and nitric oxide enhances its paracrine effects on radiation-induced intestinal injury - Hao Chen; Xiao-Hui Min; Qi-Yi Wang; Felix W. Leung; Liu Shi; Yu Zhou; Tao Yu; Chuan-Ming Wang; Geng An; Wei-Hong Sha; Qi-Kui Chen (Scientific Reports)
Abstract Conditioned medium from mesenchymal stem cells (MSC-CM) may represent a promising alternative to MSCs transplantation, however, the low concentrations of growth factors in non-activated MSC-CM hamper its clinical application. Recent data indicated that the paracrine potential of MSCs could be enhanced by inflammatory factors. Herein, we pre-activated bone-marrow-derived MSCs under radiation-induced inflammatory condition (MSCIEC-6(IR)) and investigated the evidence and mechanism for the differential effects of MSC-CMIEC-6(IR) and non-activated MSC-CM on radiation-induced intestinal injury (RIII). Systemic infusion of MSC-CMIEC-6(IR), but not non-activated MSC-CM, dramatically improved intestinal damage and survival of irradiated rats. Such benefits may involve the modulation of epithelial regeneration and inflammation, as indicated by the regeneration of intestinal epithelial/stem cells, the regulation of the pro-/anti-inflammatory cytokine balance. The mechanism for the superior paracrine efficacy of MSCIEC-6(IR) is related to a higher secretion of regenerative, immunomodulatory and trafficking molecules, including the pivotal factor IGF-1, induced by TNF-α, IL-1β and nitric oxide partially via a heme oxygenase-1 dependent mechanism. Together, our findings suggest that pre-activation of MSCs with TNF-α, IL-1β and nitric oxide enhances its paracine effects on RIII via a heme oxygenase-1 dependent mechanism, which may help us to maximize the paracrine potential of MSCs.